Dashboard Berbasis Web untuk Pemantauan Status Gizi Anak: Klasifikasi Otomatis Z-Score WHO, Visualisasi Longitudinal, dan Evaluasi Kegunaan - Rian Arie Gustaman; Andri Ulus Rahayu; Imam Taufiqurrahman; Fittur Farabi Sanaz (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2025)
This study addressed the need for timely monitoring of child nutritional status by designing, implementing, and evaluating a web-based dashboard. The system captured demographic and anthropometric records, automated status classification using World Health Organization z-scores, and visualized longitudinal growth trajectories. Development followed an iterative, user-centered process and was validated with synthetic records and formative testing by community health workers. Functional testing confirmed correct operation of data entry, classification, and reporting. Against reference calculations, category assignments matched all twenty test cases. Performance profiling indicated responsive interaction (time to first byte about 180 milliseconds; time to interactive about 1.3 seconds), and usability measured with the System Usability Scale fell in the “good” range. Findings suggested readiness for community use and a scalable foundation for future integration and field deployment.